CHEMICAL ATTRIBUTES OF PROPERTIES IN SOIL SUBMITTED TO SUCCESSIVE APPLICATIONS OF PIG SLURRY IN BRAÇO DO NORTE CITY, SANTA CATARINA STATE - COUTO, Rafael da Rosa; COMIN, Jucinei José; BEBER, Caetano Luis; URIARTE, Julio Francisco; BRUNETTO, Gustavo; BELLI FILHO, Paulo (Scientia Agraria, 2010)
In Santa Catarina (SC) State, pigs are produced in intensive system and the pig slurry generated is used as organic fertilizer in crops and pasture. This study aimed to evaluate changes of chemical attributes in soil with successive applications of pig slurry in properties located at Braço do Norte (SC) city. In September 2009 questionnaires were applied to characterize the production system of pigs and management of pig slurry in six properties in two micro regions, located at Braço do Norte (SC) city. Soil samples were collected (layer 0-20 cm) and the organic matter, pH, P, K, Al, Ca, Mg, Zn, Cu and Mn were analyzed. Successive applications of pig slurry, in the properties, in two micro regions of Braço do Norte City, Santa Catarina State, Southern Brazil, increased the content of phosphorus and potassium until very high and copper and zinc until high.